A lightweight, corrosion-resistant cement-based prefabricated component and its preparation method and use

By using modified stone powder, foaming agent and adhesive in cement-based prefabricated components, combined with microwave heating technology, the problem of easy damage and heavy weight in cold areas is solved, achieving efficient corrosion resistance and lightweight and convenient installation.

CN119320258BActive Publication Date: 2025-04-01山东高速工程检测有限公司
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411444161.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-04-01
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

Existing cement-based prefabricated components are prone to early damage in cold areas, lack of durability, and have a large weight, making it difficult to install and replace.

Method used

Lightweight corrosion-resistant cement-based prefabricated components are used. By using modified stone powder and foaming agent in the inner and outer layers of the cement-based prefabricated components, combined with adhesive and microwave heating technology, the components' anti-salt and acid corrosion resistance are improved, and the weight is reduced.

Benefits of technology

It improves the salt freezing and acid corrosion resistance of cement-based prefabricated components, extends the service life, reduces weight, and improves installation convenience and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320258B_ABST
    Figure CN119320258B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of building materials, and in particular to a lightweight, corrosion-resistant cement-based prefabricated component, a preparation method and a use thereof. The cement-based prefabricated component is composed of a matrix located in the inner layer of the cement-based prefabricated component and a fabric located in the outer layer of the cement-based prefabricated component, which are prefabricated by bonding with an adhesive and then subjected to microwave heating. The fabric is prepared by using fillers, modified stone powder, cement, etc., through colloid mill shearing treatment and filter press treatment; the matrix is ​​prepared by using foaming agent, mineral powder, sodium hydroxide, metakaolin, aggregate, polypropylene fiber, calcium lignin sulfonate, etc., through mixing, molding, steaming and demolding. The outer surface of the matrix is ​​coated with an adhesive, and the fabric is combined with the matrix by vibration extrusion molding, and then subjected to microwave heating treatment to form a cement-based prefabricated component. The cement-based prefabricated component has strong salt resistance, frost resistance and acid resistance and is light in weight, and is suitable as a building material in cold areas, including a curbstone.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a lightweight corrosion-resistant cement-based prefabricated component and a preparation method and application thereof. Background Art

[0002] With the expansion of investment in transportation infrastructure, the demand for prefabricated concrete components such as curbstones has gradually increased. According to surveys, the amount of concrete used for concrete components attached to each kilometer of highway is more than 100 cubic meters. During the rapid development of infrastructure construction in my country, this huge project has also been accompanied by a sharp increase in the consumption of concrete components.

[0003] Cement concrete curbstones are prone to surface loosening, peeling, missing edges, corner loss and other damages, especially in cold areas. After one or two years of winter and spring freeze-thaw, the cement concrete curbstones on some roads have different degrees of peeling on the surface, early damage, and partial fracture, which shortens the service life and increases the maintenance cost. In highway engineering, the durability of many auxiliary components does not meet the requirements. The number of curbstones that need to be replaced due to salt freezing damage is very alarming every year. There are great troubles and difficulties in replacement and repair, and a lot of manpower, material and financial resources are wasted. Patent documents CN116253545A, CN104926222A, and CN113929392A respectively disclose a variety of salt-resistant and frost-resistant concrete parts. However, the frost-resistant concrete parts of patent document CN116253545A require the use of expensive steel fibers, phase change materials and chloride ion curing agents. The salt-freeze resistant concrete parts of patent document CN104926222A require the use of polyurethane, water reducing agent, air entraining agent, organic membrane coating, etc. The salt-freeze resistant concrete parts of patent document CN113929392A require impregnation and other treatments. Therefore, this field still needs to improve the precast concrete parts, etc., to improve the performance of salt-freeze resistance, and enhance the long-term durability of precast concrete components. In addition, the relationship between the weight and strength of cement-based precast components leads to the current cement-based precast components usually using high-density and high-hardness materials, resulting in cement-based precast components being generally heavier, which increases the load of installation and replacement. Summary of the invention

[0004] In view of the above problems, the purpose of the present invention is to provide a lightweight, corrosion-resistant cement-based prefabricated component and a preparation method and use thereof, so as to improve the tolerance of the cement-based prefabricated component to salt, frost, acid corrosion, etc., and to improve the convenience and weight burden of the installation of the cement-based prefabricated component, so as to obtain a cement-based prefabricated component that is both lightweight and corrosion-resistant and meets the strength requirements. The cement-based prefabricated component is suitable for use as a curbstone, especially as a curbstone in cold regions, such as the northeast region of my country and the high-altitude regions in the west.

[0005] To achieve the above object, the technical solution of the present invention is as follows:

[0006] A lightweight, corrosion-resistant cement-based prefabricated component, comprising a matrix located in the inner layer of the cement-based prefabricated component and a fabric located in the outer layer of the cement-based prefabricated component, which are bonded by an adhesive and preformed by microwave heating, wherein the fabric is made of the following raw materials and water: 20 to 30 parts by weight of filler, 20 to 30 parts by weight of modified stone powder, 40 to 60 parts by weight of cement, and 1% to 3% by weight of a first surfactant of cement; wherein the preparation method of the modified stone powder comprises the following steps: heating rock asphalt powder to 200 to 220 ℃, add limestone powder in a ratio of rock asphalt powder to limestone powder (1-2): 1, stir and disperse evenly, grind at -5℃-0℃ to obtain modified stone powder; wherein the matrix is ​​made of the following raw materials and water: 5-10 parts by weight of foaming agent, 30-40 parts by weight of mineral powder, 10-15 parts by weight of sodium hydroxide, 30-40 parts by weight of metakaolin, 100-300 parts by weight of aggregate, 10-15 parts by weight of polypropylene fiber, and 1% to 3% of the total mass of mineral powder and metakaolin as a second surfactant.

[0007] Preferably, the thickness of the fabric is 1 cm to 2 cm, and more preferably, the thickness of the fabric is 1 cm to 1.5 cm.

[0008] Preferably, the filler is selected from at least one of secondary fly ash and glass microspheres;

[0009] Preferably, the strength grade of the cement used in the fabric is 52.5.

[0010] Preferably, the foaming agent is hydrogen peroxide.

[0011] Preferably, the mineral powder grade is S95, and the alumina content in the mineral powder is ≥13%.

[0012] Preferably, the aggregate is sand with a particle size of 0.07 mm to 1.2 mm.

[0013] Preferably, the second surfactant is calcium lignin sulfonate.

[0014] Preferably, the polypropylene fiber has a length of 10 mm to 20 mm.

[0015] Preferably, the first surfactant is selected from at least one of polycarboxylate water reducer, calcium lignin sulfonate, and aliphatic water reducer.

[0016] Preferably, the adhesive is epoxy resin.

[0017] The method for preparing the aforementioned lightweight corrosion-resistant cement-based prefabricated component comprises the following steps:

[0018] Fabric preparation: filler, modified stone powder, cement, a first surfactant and water are mixed with a water-cement ratio of 3 to 5 to prepare a fabric premix slurry; the fabric premix slurry is added to a colloid mill for shearing to prepare a fabric premix; the fabric premix is ​​subjected to filter pressing treatment using a filter press device to separate excess free water to prepare a fabric with a water-cement ratio of 0.15 to 0.2;

[0019] Preparation of the matrix: The foaming agent, mineral powder, sodium hydroxide, metakaolin, aggregate, polypropylene fiber, the second surfactant and water are mixed and stirred, poured into the prefabricated component mold, steamed and cured, and demolded to obtain the matrix.

[0020] Preparation of prefabricated components: apply adhesive on the outer surface of the substrate, and then use vibration extrusion molding to combine the fabric and the substrate at a pressure of 3MPa to 5MPa to obtain a preliminary processed cement-based prefabricated component; microwave heat the preliminary processed prefabricated component at 120°C to 150°C for 15s to 30s to obtain a finished cement-based prefabricated component.

[0021] Preferably, in the fabric preparation step, the pressure range of the filter press treatment is 10KN to 15KN.

[0022] Preferably, in the substrate preparation step, the temperature of the steam curing treatment is 50° C. to 80° C., and the steam curing time is 12 h to 48 h; further preferably, the temperature of the steam curing treatment is 60° C., and the steam curing time is 18 h to 24 h.

[0023] The colloid mill can be a ME600 pipeline high shear mixing emulsifier.

[0024] The filter press device can be a MZG30 / 800 stainless steel diaphragm filter press.

[0025] The aforementioned lightweight, corrosion-resistant cement-based prefabricated component is used as a curbstone.

[0026] Beneficial effects:

[0027] Firstly, the present invention improves the dispersion effect among cement particles, fillers and modified stone powder by adopting a large water-cement ratio and colloid mill shearing, thereby avoiding the problem of particle agglomeration caused by a low water-cement ratio, blocking the intrusion of sodium, potassium, sulfate and other ions by modifying the stone powder with rock asphalt powder, and squeezing out excess free water with the help of a filter press, thereby avoiding the reduction in strength of the prefabricated component fabric and improving the density of the prefabricated component fabric.

[0028] Secondly, the present invention adopts microwave heating treatment to achieve the heating of prefabricated component materials and rock asphalt materials, promote cement hydration, achieve the softening of rock asphalt materials, enhance the adhesion and wrapping of rock asphalt with other materials, thereby improving the density and durability of components.

[0029] In addition, the present invention adopts the foaming method to reduce the bulk density of the substrate, realizes the convenience of installation of the prefabricated components, and adopts the alkali excitation and steam curing methods to compensate for the low strength problem caused by the low bulk density of the substrate. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is a schematic structural diagram of the cement-based prefabricated component of the present invention. DETAILED DESCRIPTION

[0031] The product, preparation method and performance of the present invention are described below in conjunction with specific examples. As auxiliary explanations, the examples are not considered to limit the scope of protection of the present invention.

[0032] Figure 1 The schematic diagram of the structure of the cement-based prefabricated component of the present invention is shown in FIG. 1 , wherein the inner layer is the matrix, the outer layer is the outer surface, and an adhesive is applied between the matrix and the outer surface. Figure 1 The cement-based prefabricated component shown is square, but under the technical solution and basic principle of the present invention, the cement-based prefabricated component of the present invention can also be L-shaped, T-shaped, curved, etc. In the following examples, the second surfactant is calcium lignin sulfonate.

[0033] Example 1 A cement-based prefabricated component

[0034] The cement-based prefabricated component consists of a fabric + an adhesive + a matrix.

[0035] The face material is made of water and the following materials: 20 parts of filler, 20 parts of modified stone powder, 60 parts of cement, and a first surfactant (the amount of which accounts for 3% of the mass of the cement).

[0036] The first surfactant is polycarboxylate water reducer; the filler is secondary fly ash; and the cement strength grade is 52.5. The preparation process of modified stone powder is to heat the rock asphalt powder to 220°C, then add the limestone powder to the rock asphalt powder in a mass ratio of 2:1 and stir and disperse evenly, and then obtain the rock asphalt modified stone powder by low temperature grinding after mixing, and the low temperature grinding temperature is controlled at -5-0°C.

[0037] The filler, modified stone powder, cement, the first surfactant and water are mixed with a water-cement ratio of 5 to prepare a fabric premix slurry; the fabric premix slurry is added to a colloid mill for shearing treatment to prepare a fabric premix, and the fabric premix is ​​subjected to filter pressing treatment (pressure 15KN) using a filter press device to separate excess free water to prepare a fabric with a water-cement ratio of 0.15.

[0038] The matrix is ​​made of water and the following materials: 10 parts of foaming agent, 40 parts of mineral powder, 13 parts of sodium hydroxide, 40 parts of metakaolin, 300 parts of aggregate, 15 parts of polypropylene fiber, and a second surfactant (the amount of which accounts for 3% of the total mass of the mineral powder and metakaolin).

[0039] The aggregate sand particle size is 0.075mm~1.18mm single particle sand, the foaming agent is hydrogen peroxide, the mineral powder grade is S95, the alumina content in the mineral powder is ≥13%, the polypropylene fiber length is 15mm, and the surfactant is calcium lignin sulfonate.

[0040] The foaming agent, mineral powder, sodium hydroxide, metakaolin, aggregate, polypropylene fiber, the second surfactant and water are mixed and stirred, with a water-binder ratio of 0.35, and poured into the prefabricated component mold to obtain foamed concrete, which is cured by steam curing, and the foamed concrete prefabricated component matrix is ​​obtained after demoulding. The steam curing temperature is 60°C and the steam curing time is 18 hours.

[0041] Epoxy resin was used as an adhesive to be sprayed onto the outer surface of the substrate, and then the fabric was combined with the substrate by vibration extrusion molding at a pressure of 3 MPa to obtain a cement-based prefabricated component with a fabric thickness of 1.5 cm.

[0042] The obtained cement-based prefabricated component is heated by microwave to improve the bonding of the adhesive to the fabric and the substrate, wherein the microwave heating temperature is controlled at 120° C. and the insulation time is 30 seconds, thereby obtaining a finished cement-based prefabricated component.

[0043] Example 2 A cement-based prefabricated component

[0044] The cement-based prefabricated component consists of a fabric + an adhesive + a matrix.

[0045] The face material is made of water and the following materials: 30 parts of filler, 30 parts of modified stone powder, 40 parts of cement, and a first surfactant (the amount of which accounts for 1% of the mass of the cement).

[0046] The first surfactant is an aliphatic water reducer; the filler is glass beads; and the cement strength grade is 52.5. The preparation process of the modified stone powder is to heat the rock asphalt powder to 200°C, then add the limestone powder to the rock asphalt powder in a mass ratio of 1:1 and stir and disperse evenly, and then obtain the rock asphalt modified stone powder by low temperature grinding after mixing, and the low temperature grinding temperature is controlled at -5-0°C.

[0047] The filler, modified stone powder, cement, the first surfactant and water are mixed with a water-cement ratio of 3 to prepare a fabric premix slurry; the fabric premix slurry is added to a colloid mill for shearing treatment to prepare a fabric premix, and the fabric premix is ​​subjected to filter pressing treatment (pressure 10KN) using a filter press device to separate excess free water to prepare a fabric with a water-cement ratio of 0.22.

[0048] The matrix is ​​made of water and the following materials: 5 parts of foaming agent, 30 parts of mineral powder, 10 parts of sodium hydroxide, 30 parts of metakaolin, 100 parts of aggregate, 10 parts of polypropylene fiber, and a second surfactant (the amount of which accounts for 1% of the total mass of the mineral powder and metakaolin).

[0049] The aggregate sand particle size is 0.075mm~1.18mm single particle sand, the foaming agent is hydrogen peroxide, the mineral powder grade is S95, the alumina content in the mineral powder is ≥13%, the polypropylene fiber length is 15mm, and the surfactant is calcium lignin sulfonate.

[0050] The foaming agent, mineral powder, sodium hydroxide, metakaolin, aggregate, polypropylene fiber, the second surfactant and water are mixed and stirred, with a water-binder ratio of 0.3, poured into the prefabricated component mold to obtain foamed concrete, cured by steaming, and the foamed concrete prefabricated component matrix is ​​obtained after demoulding. The steaming temperature is 60°C and the steaming time is 24 hours.

[0051] Epoxy resin was used as an adhesive to be sprayed onto the outer surface of the substrate, and then the fabric was combined with the substrate by vibration extrusion molding at a pressure of 5 MPa to obtain a cement-based prefabricated component with a fabric thickness of 1.0 cm.

[0052] The obtained cement-based prefabricated component is heated by microwave to improve the bonding of the adhesive to the fabric and the substrate, wherein the microwave heating temperature is controlled at 150° C. and the insulation time is 15 s, thereby obtaining a finished cement-based prefabricated component.

[0053] Example 3 A cement-based prefabricated component

[0054] The cement-based prefabricated component consists of a fabric + an adhesive + a matrix.

[0055] The face material is made of water and the following materials: 25 parts of filler, 25 parts of modified stone powder, 50 parts of cement, and a first surfactant (the amount of which accounts for 2% of the mass of cement).

[0056] The first surfactant is calcium lignin sulfonate; the filler is secondary fly ash; and the cement strength grade is 52.5. The preparation process of the modified stone powder is to heat the rock asphalt powder to 210°C, then add the limestone powder to the rock asphalt powder at a mass ratio of 1.5:1 and stir and disperse evenly, and then obtain the rock asphalt modified stone powder by low temperature grinding after mixing, and the low temperature grinding temperature is controlled at -5-0°C.

[0057] The filler, modified stone powder, cement, the first surfactant and water are mixed with a water-cement ratio of 4 to prepare a fabric premix slurry; the fabric premix slurry is added to a colloid mill for shearing treatment to prepare a fabric premix, and the fabric premix is ​​subjected to filter pressing treatment (pressure 12KN) using a filter press device to separate excess free water to prepare a fabric with a water-cement ratio of 0.18.

[0058] The matrix is ​​made of water and the following materials: 8 parts of foaming agent, 35 parts of mineral powder, 12 parts of sodium hydroxide, 35 parts of metakaolin, 200 parts of aggregate, 13 parts of polypropylene fiber, and a second surfactant (the amount of which accounts for 2% of the total mass of the mineral powder and metakaolin).

[0059] The aggregate sand particle size is 0.075mm~1.18mm single particle sand, the foaming agent is hydrogen peroxide, the mineral powder grade is S95, the alumina content in the mineral powder is ≥13%, the polypropylene fiber length is 15mm, and the surfactant is calcium lignin sulfonate.

[0060] The foaming agent, mineral powder, sodium hydroxide, metakaolin, aggregate, polypropylene fiber, the second surfactant and water are mixed and stirred, and the water-binder ratio is 0.32, and poured into the prefabricated component mold to obtain foamed concrete, which is cured by steam curing, and the foamed concrete prefabricated component matrix is ​​obtained after demoulding. The steam curing temperature is 60°C and the steam curing time is 21 hours.

[0061] Epoxy resin was used as an adhesive to be sprayed onto the outer surface of the substrate, and then the fabric was combined with the substrate by vibration extrusion molding at a pressure of 4 MPa to obtain a cement-based prefabricated component with a fabric thickness of 1.2 cm.

[0062] The obtained cement-based prefabricated component is heated by microwave to improve the bonding of the adhesive to the fabric and the substrate, wherein the microwave heating temperature is controlled at 140° C. and the insulation time is 20 s, thereby obtaining a finished cement-based prefabricated component.

[0063] Comparative Example 1 Cement-based prefabricated components

[0064] The cement-based prefabricated component of this comparative example is different from that of Example 1 in that the rock asphalt powder is directly added to the fabric without being pre-modified with the limestone powder. The rest is the same as that of Example 1.

[0065] Comparative Example 2 Cement-based prefabricated components

[0066] The cement-based prefabricated component of this comparative example is different from that of Example 1 in that limestone powder is directly added to the fabric, and rock asphalt powder and pre-modification treatment are not used. The rest is the same as that of Example 1.

[0067] Comparative Example 3 Cement-based prefabricated components

[0068] The cement-based prefabricated component of this comparative example is different from that of Example 1 in that no adhesive is used to bond the surface material to the substrate, and the rest is the same as that of Example 1.

[0069] Comparative Example 4 Cement-based prefabricated components

[0070] The cement-based prefabricated component of this comparative example is different from that of Example 1 in that microwave treatment is not used, and the rest is the same as that of Example 1.

[0071] With reference to the building materials industry standard of the People's Republic of China "Concrete Kerb" (JCT-899-2016) and "Concrete Durability Test and Evaluation Standard" (JGJT193-2009), the water absorption, frost resistance, salt-freeze resistance and sulfate resistance of the cement-based prefabricated components of the embodiment and the comparative example were tested, and the results are shown in Table 1.

[0072] Table 1 Properties of cement-based precast components

[0073]

[0074]

[0075] The test results show that the cement-based prefabricated components in Examples 1-3 have a lower water absorption rate, and their anti-freeze performance, salt-freeze resistance, and sulfate resistance are much better than those of the cement-based prefabricated components in the comparative example, and exceed the standard requirements in the specification.

[0076] On the contrary, the cement-based prefabricated components of Comparative Example 1 were not modified, and the density of the rock asphalt powder itself was relatively small, causing it to float on the surface of the fabric in a suspended state and fail to be effectively dispersed in the fabric, forming defects in the fabric, which had an adverse effect on the performance of the prefabricated components, causing indicators such as the salt erosion resistance of the prefabricated components to far exceed the specified values ​​​​of the specifications and fail to meet the specified standards.

[0077] Although the cement-based prefabricated components of Comparative Example 2 do not use rock asphalt powder and their water absorption rate meets the requirements of the specifications, their frost resistance and salt-freeze resistance exceed the specification values, mainly because the intrusion of external water and salt ions leads to the reduction of performance.

[0078] For the cement-based prefabricated components of Comparative Example 3, no adhesive was used to bond the base and the fabric. The water absorption index met the requirements. However, after antifreeze and anti-salt freezing, the fabric and the base were separated, and the fabric peeling far exceeded the specification value.

[0079] The cement-based prefabricated components of Comparative Example 4 were not microwave treated, and the bonding effect of the adhesive was relatively small, and the intrusion of salt ions could not be effectively blocked, and the anti-freeze and anti-salt-freeze indicators exceeded the standard values.

[0080] The flexural strength and compressive strength of the cement-based prefabricated components of Examples 1-3 were further tested, and the flexural strength grades all reached the C level required by the specification. f The compressive strength grade of the steel pipes reaches the C45 grade required by the specification.

Claims

1. A lightweight, corrosion-resistant cement-based prefabricated component, characterized in that: The cement-based prefabricated component is composed of a matrix located in the inner layer of the cement-based prefabricated component and a fabric located in the outer layer of the cement-based prefabricated component, which are bonded by an adhesive and preformed by microwave heating; the fabric is made of the following raw materials and water: 20-30 parts by weight of filler, 20-30 parts by weight of modified stone powder, 40-60 parts by weight of cement, and 1%-3% by weight of a first surfactant of cement; the preparation method of the modified stone powder comprises the following steps: heating the rock asphalt powder to 200-220°C, The green powder and limestone powder are added in a mass ratio of (1-2):1, and the limestone powder is stirred and dispersed evenly, and ground at -5°C-0°C to obtain modified stone powder; wherein the matrix is ​​made of the following raw materials and water: 5-10 parts by weight of a foaming agent, 30-40 parts by weight of mineral powder, 10-15 parts by weight of sodium hydroxide, 30-40 parts by weight of kaolin, 100-300 parts by weight of aggregate, 10-15 parts by weight of polypropylene fiber, and 1%-3% of the total mass of the mineral powder and kaolin as a second surfactant.

2. A lightweight, corrosion-resistant cement-based prefabricated component according to claim 1, characterized in that: The filler is selected from at least one of secondary fly ash and glass beads.

3. A lightweight, corrosion-resistant cement-based prefabricated component according to claim 1, characterized in that: The strength grade of the cement used in the fabric is 52.

5.

4. A lightweight, corrosion-resistant cement-based prefabricated component according to claim 1, characterized in that: The foaming agent is hydrogen peroxide; the second surfactant is calcium lignin sulfonate; and the adhesive is epoxy resin.

5. The lightweight, corrosion-resistant cement-based prefabricated component according to claim 1, characterized in that: The mineral powder grade is S95, and the alumina content in the mineral powder is ≥13%; the aggregate is sand with a particle size of 0.07mm~1.2mm; and the polypropylene fiber length is 10mm~20mm.

6. The lightweight, corrosion-resistant cement-based prefabricated component according to claim 1, characterized in that: The first surfactant is selected from at least one of polycarboxylate water reducer, calcium lignin sulfonate, and aliphatic water reducer.

7. The method for preparing a lightweight, corrosion-resistant cement-based prefabricated component according to any one of claims 1 to 6, characterized in that: The steps include: Fabric preparation: filler, modified stone powder, cement, a first surfactant and water are mixed with a water-cement ratio of 3-5 to prepare a fabric premix; the fabric premix is ​​added to a colloid mill for shearing to prepare a fabric premix; the fabric premix is ​​subjected to filter pressing by a filter press device to separate excess free water to prepare a fabric with a water-cement ratio of 0.15-0.2; Preparation of the matrix: mixing and stirring the foaming agent, mineral powder, sodium hydroxide, metakaolin, aggregate, polypropylene fiber, the second surfactant and water, pouring into the prefabricated component mold, steaming and curing, and demolding to obtain the matrix; Preparation of prefabricated components: apply adhesive on the outer surface of the substrate, and then use vibration extrusion molding to combine the fabric and the substrate at a pressure of 3MPa~5MPa to obtain a preliminary processed product of a cement-based prefabricated component; microwave heat and keep the preliminary processed product of the prefabricated component at 120℃~150℃ for 15s~30s to obtain a finished cement-based prefabricated component.

8. The method for preparing a lightweight, corrosion-resistant cement-based prefabricated component according to claim 7, characterized in that: In the fabric preparation step, the pressure range of the filter press treatment is 10KN~15KN.

9. The method for preparing a lightweight, corrosion-resistant cement-based prefabricated component according to claim 7, characterized in that: In the substrate preparation step, the temperature of the steam curing treatment is 50° C. to 80° C., and the steam curing time is 12 h to 48 h.

10. Use of the lightweight, corrosion-resistant cement-based prefabricated component according to any one of claims 1 to 6 as a curbstone.

Citation Information

Patent Citations

  • Formula of salt-frost-resistant crushed stone aggregate concrete curb and preparation method of curb

    CN104926222A

  • Salt-freezing-resistant high-performance precast concrete curb and preparation method thereof

    CN113929392A

  • Low-shrinkage super-anti-freezing coarse aggregate ultra-high performance concrete pavement layer and preparation method thereof

    CN116253545A

  • Prefabricated foamed lightweight insulation mineral polymer wallboard and preparation method thereof

    CN109206114A

  • Asphalt concrete prefabricated part based on solid waste material and preparation method of asphalt concrete prefabricated part

    CN113998923A